2018
DOI: 10.1186/s12991-018-0175-5
|View full text |Cite
|
Sign up to set email alerts
|

Strength-based assessment for future violence risk: a retrospective validation study of the Structured Assessment of PROtective Factors for violence risk (SAPROF) Japanese version in forensic psychiatric inpatients

Abstract: BackgroundThe Structured Assessment of PROtective Factors for violence risk (SAPROF) was recently developed as a strength-based addition to the risk assessment of future violent behavior. We examined the interrater reliability and predictive accuracy of the SAPROF for violence in forensic mental health inpatient units in Japan.MethodsThis retrospective record study provides an initial validation of the SAPROF in a Japanese sample of 95 forensic psychiatric inpatients from a complete 2008–2013 cohort. Violent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…In addition, the SAPROF-YV provided incremental predictive validity on top of risk factors for general reoffending. Several studies among adult offenders demonstrated incremental predictive validity for violent reoffending of the SAPROF protective factors (adult version) over well-established risk factors (e.g., those in the HCR-20) for various offender samples (Coupland, 2015;Kashiwagi et al, 2018;De Vries Robbé et al, 2013). Our results support a small but growing body of empirical evidence for the added value of protective factors over risk assessment based on risk factors alone.…”
Section: The Added Value Of Protective Factorssupporting
confidence: 74%
“…In addition, the SAPROF-YV provided incremental predictive validity on top of risk factors for general reoffending. Several studies among adult offenders demonstrated incremental predictive validity for violent reoffending of the SAPROF protective factors (adult version) over well-established risk factors (e.g., those in the HCR-20) for various offender samples (Coupland, 2015;Kashiwagi et al, 2018;De Vries Robbé et al, 2013). Our results support a small but growing body of empirical evidence for the added value of protective factors over risk assessment based on risk factors alone.…”
Section: The Added Value Of Protective Factorssupporting
confidence: 74%
“…Although neither of these studies analyzed the SAPROF’s predictive validity, the other four studies did. The Japanese and Irish studies found the SAPROF to have good and incremental predictive validity, whereas the Swiss studies reported only moderate predictive validity (i.e., total score AUC value = .70 for sexual/violent recidivism, total score AUC value = .64 for general recidivism) and no added value compared with other risk assessments (Abbiati et al, 2017, 2019; Abidin et al, 2013; Kashiwagi et al, 2018). To the best of our knowledge, the SAPROF’s internal validity has never been analyzed in detail.…”
Section: The Structured Assessment Of Protective Factors For Violencementioning
confidence: 99%
“…First, the vagueness of some START strength items may originate from the “lack of conceptual certitude around the relationship between protective and risk factors” ( 48 ). This reasoning may be supported by previous findings that assessment tools with separate items and unambiguous definitions for protective factors, such as SAPROF and SAVRY, tend to perform better in demonstrating incremental validity ( 49 51 ). Second, strength scores may be more predictive of positive results, such as job attainment and personal recovery, than merely non-negative results such as absence of violence.…”
Section: Discussionmentioning
confidence: 56%